The Factors Affecting Cooperation and the Moderating Effect of Technological Turbulence - Arthur Tunggul Siahaan; Eko Suhartanto; Christiana Tercia (INTERNATIONAL RESEARCH JOURNAL OF BUSINESS STUDIES, 2021)
This present study examines the effect of technological turbulence in driving cooperation, the role of non-economic satisfaction in mediating between focal constructs of relationship marketing (RM) with cooperation, and the effect of interpersonal commitment on interorganizational commitment. The findings show that high technological turbulence dampens the positive relationship of two focal constructs of RM, non-economic satisfaction mediates focal constructs of RM and cooperation, and interpersonal commitment influences interorganizational commitment. The study uses empirical data from business-to-business (B2B) ICT resellers in Indonesia to test the hypotheses developed. A structured questionnaire via an online platform is used as a research instrument with one hundred and one companies participating. https://doi.org/10.21632/irjbs.14.2.171-186